The Role Of KKN Students In Making Trash Bins In Talang Perapat Village, West Seluma District - Saputra, Jimmiylin Willso; Cahyani, Jingga Febbya; Listika, Listika; Yanti, Rina Trisna; Susena, Karona Cahya; Handayani, Tita (Universitas Dehasen Bengkulu, 2025)
This study aims to describe the implementation and impact of a waste bank The The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student dedication to society aimed at applying academic knowledge while supporting rural development. One of the KKN activities in Talang Perapat Village, Seluma Barat District, was the construction of permanent waste bins to raise community awareness about proper waste management and environmental cleanliness. This study employed a descriptive qualitative approach using observation, interviews, and documentation techniques. The informants consisted of the village head, community leaders, and residents involved in the activities. The findings indicate that the program received positive responses, successfully encouraged behavioral changes in waste sorting, and increased active participation in maintaining environmental cleanliness. The program also strengthened social bonds among residents, fostered the spirit of mutual cooperation, and served as a good example of collaboration between KKN students, the community, and the village government. The success of this program is expected to inspire other villages to develop community-based waste management initiatives.